2020
DOI: 10.1038/s41467-020-15308-7
|View full text |Cite
|
Sign up to set email alerts
|

Rac1 activates non-oxidative pentose phosphate pathway to induce chemoresistance of breast cancer

Abstract: Resistance development to one chemotherapeutic reagent leads frequently to acquired tolerance to other compounds, limiting the therapeutic options for cancer treatment. Herein, we find that overexpression of Rac1 is associated with multi-drug resistance to the neoadjuvant chemotherapy (NAC). Mechanistically, Rac1 activates aldolase A and ERK signaling which up-regulates glycolysis and especially the non-oxidative pentose phosphate pathway (PPP). This leads to increased nucleotides metabolism which protects bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(80 citation statements)
references
References 60 publications
(85 reference statements)
1
79
0
Order By: Relevance
“…related to the progress of human breast cancer [26][27][28][29][30][31]. These data clearly provide useful information for the resistance development of breast cancer.…”
Section: Plos Onementioning
confidence: 73%
“…related to the progress of human breast cancer [26][27][28][29][30][31]. These data clearly provide useful information for the resistance development of breast cancer.…”
Section: Plos Onementioning
confidence: 73%
“…It has now become increasingly evident that benefits of glycolysis extend beyond metabolism and role of altered glycolysis has been implicated in transcriptional regulation (10), epigenetic regulation (11,12), immune-escape (13), cell cycle (14), mitotic spindle (15), metastasis (16), and inflammation (17). Moreover, aerobic glycolysis and associated pathways contribute to chemoand radio-resistance in cancer (18)(19)(20). Combinatorial treatments with compounds inhibiting glycolysis have shown synergy in decreasing triple-negative breast cancer cell viability (21).…”
Section: Introductionmentioning
confidence: 99%
“…Another study found that ERK activation via a member of small G proteins Rac1 increases nucleotide metabolism in breast cancer cells and protects against chemotherapy-induced cytotoxicity and DNA damage. Rac1 is also upregulated in chemoresistant breast cancer and correlates with poor prognosis [ 139 ].…”
Section: The Cxcl12/cxcr4-induced Therapy Resistance In Breast Camentioning
confidence: 99%